Scot Harvath : Black List - Book 11 - Thor, Brad (New York : Emily Bestler Books/Atria, 2012)
When his name is added to a secret government list of individuals slated for assassination, counterterrorism operative Scot Harvath engages in a high-stakes game of survival while struggling to prevent a terrorist attack and learn who has framed him for treason.
Keywords: Terrorism -- Fiction -- Prevention; Intelligence service -- Fiction; Mystery fiction